A Study of Student-Teachers' Emotional Experiences and Their Development of Professional Identities - Chen, Zehang; Sun, Yin; Jia, Zhenhui (Frontiers in Psychology, 2022)
A reciprocal relation has been identified between teacher emotion and teacher professional identity. However, the underlying mechanism explaining this complex interaction remains underexplored. Moreover, limited attention has been paid to the emotional dimension of student-teachers’ professional identity development during university coursework. To bridge this gap, the present study explores how student-teachers’ emotions reciprocally interact with their professional identities, drawing data from questionnaires, reflections, and interviews with students taking ELT methodology related courses in a teacher preparation university. Both quantitative and qualitative data together delineated the intertwined trajectories of student-teachers emotional experiences and development of professional identity in the process of learning to become teachers. Mainly triggered by course-related factors, student-teachers experienced a wide array of emotions, of which the polarity and intensity were determined and mediated by their goals and actions deriving from these professional identities. These aroused emotions, in turn, signaled the developmental process of professional identity, and promoted or hindered emerging identities. This paper concludes with some implications for initial teacher education programs.